ASSOCIATION OF SPONTANEOUS HEPATIC ENCEPHALOPATHY IN HIGH PROTEIN DIET CONSUMER PATIENTS OF CHRONIC LIVER DISEASE.: http://doi.org/10.46536/jpumhs/2023/13.03.455 - Rehmatullah Bhatti1 , Abdul Hafeez Soomro2 , Jawaid Iqbal3 , Adil Hassan4 , Ubedullah Bughio5 , Bushra Qadir6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
OBJECTIVE: To determine the association of spontaneous hepatic encephalopathy in high protein diet consumer patients of chronic liver disease CLD. STUDY SETTING: This descriptive study was carried out at gastroenterology department of Asian Institute of Medical Sciences Sindh Pakistan. STUDY DURATION: Six months from April 2019 to October 2019. METHODS: All the individuals admitted in the gastroenterology department with hepatic encephalopathy, of any gender who were 18 years of age or older were included. After takin complete medical history and clinical examination, patients were evaluated regarding rich protein diet consumption to observe the high protein diet consumption as a critical element in the development of hepatic encephalopathy. The information was gathered exclusively through a study proforma, and data analysis was conducted using SPSS version 26. RESULTS: A total of 92 patients of hepatic encephalopathy with average age of 54.36+11.3 years with male predominance were studied. Hepatitis C was the commonest etiological factors of the chronic liver disease. High-protein diet exhibited a reduced occurrence of hepatic encephalopathy, with rates of 3.3% for grade-I, 7.6% for grade-II, 4.3% for grade-III, and 4.3% for the grade-IV, in contrast to the usual diet group. Fewer patients in the high protein diet group experienced infection 3.3% compared to the usual diet group 34.8% p-0.050. Furthermore, the high protein diet group showed the significantly lower rate of AKI 1.1% compared to the usual diet group 23.9%, p- 0.034. CONCLUSION: Hepatic encephalopathy and other complications were highly prevalent in low protein diet compared to the rich protein diet. It was observed that the rich best nutritional diet is decrease the disease prognosis compared to the formal diet.